Development of Instructional Materials for Introduction to Algebraic Structures: Ring Theory with Guided Discovery - Prihadi Kurniawan; Agus Wayan Yulianto (Urogram Studi Pendidikan Matematika, Universitas IVET, 2023)
This study presents the development of Teaching Materials for Introduction to Algebraic Structures: Ring Theory with Guided Discovery, addressing the need for comprehensive instructional resources in abstract algebra courses. Following the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation), the research systematically creates and refines the Teaching Materials. The resulting resource includes a title page, carefully crafted learning objectives aligned with the desired Student Learning Outcomes (SLP), and well-organized content arranged into 12 chapters. Each chapter incorporates student learning guides and engaging activities, encouraging active participation and independent exploration. The Teaching Materials undergo rigorous validation, with results indicating a validity level of 88%, meeting the necessary criteria for instructional effectiveness. Based on the evaluation conducted at the final stage of the study, the Teaching Materials demonstrate high practicality, scoring 87%, and are deemed effective with a quality rating of 66%. This study contributes significantly to the field of mathematics education by addressing the need for effective lecture companions in introductory algebraic structures courses. By incorporating guided discovery techniques, the developed Teaching Materials foster increased student activity and knowledge construction. The utilization of the ADDIE development model ensures a systematic and well-structured approach to material creation. The comprehensive organization of content, along with the inclusion of student learning guides and activities, provides a cohesive and interactive learning experience for students. The validation and evaluation results further underscore the efficacy of the Teaching Materials, affirming their validity and practicality in promoting enhanced student learning outcomes. These findings highlight the potential of the Teaching Materials for Introduction to Algebraic Structures: Ring Theory with Guided Discovery to positively impact algebraic structures education and contribute to the pedagogical advancement in mathematics instruction. Keywords: guided discovery, teaching material development, ring theory.